Pengaruh Model Teams Games Tournament Berbantuan Aplikasi Kahoot Terhadap Hasil Belajar IPAS Siswa Kelas IV - Rina, Winda Pebrilia Cessa; Yusnia (JURIDIKDAS, 2024)
The purpose of this study was to determine the effect of Teams Games Tournament model assisted by Kahoot application on IPAS learning outcomes of grade IV students. This type of research is quantitative. The research method used was a pseudo-experiment with The Matching Only Pretest- Posttest Control Group Design. The research population was SDN Gugus XII Bengkulu City which is accredited B. The samples of this study were fourth grade students of SDN 99 as the experimental class and SDN 35 as the control class with the sampling technique using Total Sampling. The research instrument used was a test of learning outcomes in the knowledge aspect in the form of multiple choice questions totaling 10 items given through Pretest and Posttest. The type of data analysis technique in this research is quantitative analysis using descriptive statistics, prerequisite test analysis. Based on data analysis obtained average results on IPAS learning experimental class (73.57) and control class (54.07) so that the average learning outcomes of the experimental class class are greater than the control class (73.57> 54.07). The results of hypothesis testing using Independent Sample t-test obtained sig. (2-tailed) of 0.000 <0.05, then Ha is accepted. Based on this, it can be concluded that the Teams Games Tournament (TGT) type cooperative learning model assisted by the kahoot application has a positive effect on the learning outcomes of IPAS grade IV students.